A Mathematical Study on Measles Disease in Pakistan - Ananthaswamy, V.; Shruthi, M. (Journal of Applied Nonlinear Dynamics, 2026)
This study uses actual data from Pakistan to investigate an established mathematical framework that describes the dynamics and epidemiology of measles transmission. Sanitation and immunization are taken as mitigating strategies in the model. The primary model’s six components are Susceptible, Recovered, Infected, Exposed, Hospitalized, and Vaccinated that can be addressed semi-analytically using the homotopy analysis approach. To show the influence of various model parameter categories including the frequency of hospitalized persons with measles visit due to complications, rate of vaccinating susceptible class and recruitment rate into susceptible class, graphical illustrations are provided. The outcomes show that this approach is the most practical, easy to use, and efficient. A satisfactory match is obtained by comparing the findings with the numerical simulation (MATLAB). This technique will be extended to tackle epidemic models especially, SIR, SEIR, SVIR, SVEIR,SLVEIR based on malaria, chikungunya, tuberculosis, HIV, hepatitis A virus, typhoid, Ebola, Cholera etc.